2021
DOI: 10.3892/etm.2021.11029
|View full text |Cite
|
Sign up to set email alerts
|

Short vs. long intramedullary nail systems in trochanteric fractures: A randomized prospective single center study

Abstract: In unstable pertrochanteric fractures, there are still debates regarding the complications and long-term benefits after internal fixation using short or long cephalomedullary nails. Therefore, a study was developed regarding this idea. From May 2017 to April 2020, 61 patients with unstable (AO 31-A2) and intertrochanteric fractures (AO 31-A3) were surgically operated on. During follow-up, 8 patients were excluded (lost or deceased). A total of 26 patients received internal short nail system fixation and 27 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Overall, no difference in general failure and reoperation rates between the nail groups was found in the systematic reviews/meta-analysis studies, and similar findings were reported in 5 of the additional articles analyzed. 19,27,31,34,36 Peri-implant fracture rates reported in the meta-analyses were higher for the short nails with a rate of 1.97% compared with 0.64% for the long nails, 17 although this difference was not significant. Similar findings were reported in 4 of the additional studies.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Overall, no difference in general failure and reoperation rates between the nail groups was found in the systematic reviews/meta-analysis studies, and similar findings were reported in 5 of the additional articles analyzed. 19,27,31,34,36 Peri-implant fracture rates reported in the meta-analyses were higher for the short nails with a rate of 1.97% compared with 0.64% for the long nails, 17 although this difference was not significant. Similar findings were reported in 4 of the additional studies.…”
Section: Resultsmentioning
confidence: 90%
“…19,27,31,36 However, the long nails were associated with increased estimated blood loss (EBL) and longer operative time. 17,19,27,31,[34][35][36] Interestingly, one study demonstrated a weighted mean difference of 17.57 minutes in operative time in favor of the short CMN group (P , 0.05) and estimated 60 mL reduced EBL. 17 No difference between the 2 nail groups was reported for mean length of hospitalization, 31,34,36 1 year mortality rate, 17,27,31,34,36 nonmechanical complication rate, 1,27,31,36 and patient-reported outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations